Методы одномерного поиска - Северин, Валерий Петрович (НТУ "ХПИ", 2012)
Рассмотрены теория и методы одномерного поиска. Изложена теория необходимых и достаточных условий экстремума функции одной переменной. Приведены обоснование построения, теоретическое описание и алгоритмы более десяти основных методов одномерного поиска. Представленные алгоритмы позволяют облегчить изучение методов и ускорить выполнение лабораторных работ. Даны задания для лабораторных работ. Предназначено для студентов технических специальностей.

The theory and methods of one-dimensional search are considered. The theory of necessary and sufficient conditions for an extremum of a function of one variable is presented. Justification of the construction, theoretical description and algorithms of more than ten basic methods of one-dimensional search are given. The presented algorithms make it possible to facilitate the study of methods and to accelerate the performance of laboratory work. Tasks for laboratory work are given. It is intended for students of technical specialties.
Methods of one-dimensional search
Keywords: методы оптимизации; одномерный поиск; алгоритмы одномерной оптимизации; метод дихотомии; метод золотого сечения; optimization methods; one-dimensional search; one-dimensional optimization algorithms; dichotomy method; golden section method